Modelling and Simulation of the Electrical Vehicle Using Matlab and Verifying it by Driving Cycles - Maaz Mufti, Gussan; Ur Rehman, Mobeen; Abdul Basit, Dr. (International Journal of Engineering and Technology, 2018)
Modelling of the Electric Vehicle is analyzed in this paper to evaluate the performance and range of the EV. The indigenous platform of MATLAB has been used to model and simulate the different scenarios of range covered by the EV by varying the accessory power associated with them. The mathematical system was further verified by simulating the standard drive cycles for different regions of the world including the standard drive cycle of U.S.A. and E.U. These results show that the power of the accessories associated with the Electric Vehicles plays a major role in deciding the distances covered by it. A suitable selection can help to increase the range of the Electric Vehicles.Â Â Â Â Â Â Â